Hysteresis Phenomena of Moisture Sorption Isotherm in Amylose, Amylopectin, Protein, and Cellulose - Nur Wulandari; Soewarno T Soekarto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Hysteresis phenomena of four basic food compounds (amylose, amylopectin, casein, and cellulose) were studied after 9 days equilibration in descicators at 28oC. Adsorption experiments started from 2% moisture content and desorption from wetted samples with excessive moisture. In starch and protein, the hysteresis occurred in the middle range of the sorption isotherm in the range of 10 - 90% RH and no hysteresis at the lowest and highest ranges of RH. While in cellulose hysteresis started at about 10% RH and was increasing to the saturated RH. Analyses of stratified bound water using sorption isotherm data revealed that from the four samples, the desorption monolayer and secondary bound water fractions were higher than those of adsorption. However, the tertiary bound water fractions of desorption were lower than those of adsorption, except from the cellulose sample. Key words : Hysteresis, isotherm, starch, protein, and cellulose